2022
DOI: 10.36253/bae-9552
|View full text |Cite
|
Sign up to set email alerts
|

Italian farms during the COVID-19 pandemic: main problems and future perspectives. A direct analysis through the italian FADN

Abstract: The spread of the COVID-19 virus in Italy during the first phasis of the pandemic (February-May 2020) has caused a large-scale crisis, with an almost immediate decrease of industrial production and a consequent contraction in domestic consumption and external trade. However, the issue of food security was immediately recognized as one of the most sensitive, so that the Government has decreed the priority role of the food system, which has been included among those considered fundamental services and economical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…[4] evaluated the impact of COVID-19 on poverty in Tanzania through a microsimulation with a social accounting matrix and found that poverty increased, and inequality decreased. Concerning agritourism, evaluations of the impact of COVID-19 on agritourism were conducted from the supply and demand sides [5][6][7][8][9][10]. Ref.…”
Section: Impact Of Covid-19 On Agritourism: Both Negative and Positivementioning
confidence: 99%
See 1 more Smart Citation
“…[4] evaluated the impact of COVID-19 on poverty in Tanzania through a microsimulation with a social accounting matrix and found that poverty increased, and inequality decreased. Concerning agritourism, evaluations of the impact of COVID-19 on agritourism were conducted from the supply and demand sides [5][6][7][8][9][10]. Ref.…”
Section: Impact Of Covid-19 On Agritourism: Both Negative and Positivementioning
confidence: 99%
“…Ref. [8] investigated Italian Farm Accountancy Data Network (FADN) data and observed that 37% of farms had a significant liquidity crisis, and 60% of them had decreases in revenue. On the demand side, [9] studied Polish agritourism farms in 2021 and noted that well-educated and well-off city residents were the main customers of agritourism and that the relatively low risk of COVID-19 infection was an important reason for choosing agritourism.…”
Section: Impact Of Covid-19 On Agritourism: Both Negative and Positivementioning
confidence: 99%
“…This result is in contrast to findings from other studies conducted in different contexts. Cesaro et al (2022), for example, found that medium-large farms in Italy expressed greater concern about the negative consequences of COVID-19 in the short term than small farms. Having a land ownership title or holding the right to use it played an important role in cushioning the negative COVID-19 impact.…”
Section: Farm Income Changementioning
confidence: 99%
“…2 Indeed, it was initially expected that farming experienced less direct effects, except where hired labor was important, although interlinkages with the other segments of the chain may have caused income losses and production disruption (Swinnen, 2020). 3 For instance, Cesaro et al (2022) found that financial liquidity and repairment of equipment and machinery were the difficulties most reported by farmers in Italy in the short run.…”
Section: Introductionmentioning
confidence: 99%